2013
DOI: 10.1063/1.4817374
|View full text |Cite
|
Sign up to set email alerts
|

A volume-of-fluid formulation for the study of co-flowing fluids governed by the Hele-Shaw equations

Abstract: We present a computational framework to address the flow of two immiscible viscous liquids which co-flow into a shallow rectangular container at one side, and flow out into a holding container at the opposite side. Assumptions based on the shallow depth of the domain are used to reduce the governing equations to one of Hele-Shaw type. The distinctive feature of the numerical method is the accurate modeling of the capillary effects. A continuum approach coupled with a volume-of-fluid formulation for computing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…where the first term indicates the principal radii of curvature of the wave profile ζ and the second term represents the out-of-plane curvature of the meniscus which can also contribute to the surface tension force (see figure 1). For regular Hele-Shaw flow, when multi-phase flow occurs, the out-of-plane interface shape is always assumed to be semicircular and the contact angle θ is naturally 180 • (Saffman & Taylor 1958;McLean & Saffman 1981;Park & Homsy 1984;Afkhami & Renardy 2013). Nevertheless, this assumption is not appropriate for Faraday waves in Hele-Shaw cells.…”
Section: Gap-averaged Equationsmentioning
confidence: 99%
“…where the first term indicates the principal radii of curvature of the wave profile ζ and the second term represents the out-of-plane curvature of the meniscus which can also contribute to the surface tension force (see figure 1). For regular Hele-Shaw flow, when multi-phase flow occurs, the out-of-plane interface shape is always assumed to be semicircular and the contact angle θ is naturally 180 • (Saffman & Taylor 1958;McLean & Saffman 1981;Park & Homsy 1984;Afkhami & Renardy 2013). Nevertheless, this assumption is not appropriate for Faraday waves in Hele-Shaw cells.…”
Section: Gap-averaged Equationsmentioning
confidence: 99%
“…We use a volumeof-fluid (VOF) based method to directly solve the governing equations. Our numerical model, described in detail by Afkhami and Renardy (2013), has the distinctive feature of being capable of, accurately and robustly, modeling the surface tension force. In addition, the accurate interface reconstruction, the second-order curvature computation, and the use of adaptive mesh refinement allow for resolved description of the interface, enabling us to investigate the complex features of interface profiles extracted from experiments, which was not possible in prior studies.…”
Section: Computational Frameworkmentioning
confidence: 99%
“…Use of the harmonic mean in place of the arithmetic mean was first highlighted when considering heat transfer through two materials of differing thermal conductivity (Patankar, 1980). Furthermore, it has been demonstrated that the harmonic mean viscosity is an appropriate parameter to use in certain classes of multiphase flow problem (Wörner, 2012), such as the flow of two immiscible liquids in a 2D Hele-Shaw cell (Afkhami and Renardy, 2013).…”
Section: The Volume Of Fluid (Vof) Methodsmentioning
confidence: 99%